“Testicular concentrations of metals and metalloids in dogs from the ‘Land of Fires’ (Campania Region, Italy): A preliminary morphological, chemical and molecular study” - Lorenzo Riccio; Maria De Falco; Marco Trifuoggi; Claudia Cucolo; Flavia Conte; Teresa Chianese; Nicola Ambrosio; Angelo Spada; Evaristo Di Napoli; Orlando Paciello; Luigi Rosati (Environmental Toxicology and Pharmacology, 2026)

Cardoon cell cultures as a biofactory for extracellular vesicles with antisteatotic activity in an in vitro model of non-alcoholic fatty liver disease - Elisa Cappetta; Monica De Palma; Vincenzo Vestuto; Emanuele Rosa; Marisa Conte; Maria Rosaria Miranda; Mariapia Vietri; Francesca Mensitieri; Pablo Martínez-Vicente; Valentina Santoro; Ornella Moltedo; Pietro Campiglia; et al. (Food Research International, 2026)

Relationship between frailty and disease progression in Parkinson’s disease: a 3-year longitudinal study - Matteo Costanzo; Marco Canevelli; Maria Ilenia De Bartolo; Martina Valletta; Francesco Marchet; Marco Toccaceli Blasi; Giorgio Leodori; Antonella Conte; Giuseppe Bruno; Giovanni Fabbrini; Daniele Belvisi (GeroScience, 2026)
Parkinson’s disease (PD) shows substantial variability in presentation and progression. Frailty, a multidimensional construct reflecting biological aging, is a determinant of clinical outcomes in several neurodegenerative disorders. While cross-sectional studies suggest that frailty modulates the clinical phenotype of PD, affecting motor and non-motor symptoms, its longitudinal prognostic relevance remains unclear. In this 3-year, single-center cohort study, we investigated whether frailty, measured using a validated 50-item frailty index (FI), predicts clinical progression, motor complications, and mortality in a cohort of 109 PD patients. Clinical assessment included MDS-UPDRS parts III and IV, Non-Motor Symptoms Scale, Hoehn & Yahr stage, Montreal Cognitive Assessment, and levodopa equivalent daily dose (LEDD). Associations between baseline FI and follow-up outcomes were examined using simple and multiple linear regression models. Patients were stratified into three frailty groups at baseline to examine group-level differences in clinical progression and mortality, which were assessed using mixed-effects models and contingency analyses. Higher baseline FI independently predicted greater severity of treatment-related motor complications at follow-up ( β = 8.3; p = 0.04) and greater worsening of these complications over time ( β = 11.4; p = 0.017) and showed trends toward greater non-motor symptom burden and cognitive decline. No significant association was observed between baseline FI and motor progression. Patients classified as frail at baseline displayed greater clinical deterioration across multiple domains, higher LEDD requirements, and had increased mortality (χ 2 = 16.5, p < 0.001) compared to less frail counterparts. In conclusion, frailty predicts worse clinical trajectories and increased mortality in PD, supporting its utility as a prognostic biomarker. Incorporating frailty assessment into routine care may improve risk stratification and guide personalized therapeutic approaches in PD patients.

Modeling the quality decay kinetic of encapsulated ground coffee - Marco Lopriore; Marika Valentino; Giulia Ravaioli; Maria Cristina Nicoli; Amalia Conte; Matteo Alessandro Del Nobile (Journal of Food Engineering, 2026)

Water vapor transmission rate prediction: The case-study of a biopolymer-based capsule for food applications - Marco Lopriore; Michele Libralato; Giovanni Cortella; Sergio Maiandi; Maria Cristina Nicoli; Amalia Conte; Matteo Alessandro Del Nobile (Food Packaging and Shelf Life, 2025)

Hormonal protocol for cervical dilation modifies the protein profile of uterine lavage recovered from superovulated ewes - Juliana Dantas Rodrigues Santos; Yara Martins da Silva; Luís Felipe Costa Ramos; Fábio César Sousa Nogueira; Carlos Adam Conte Junior; Ribrio Ivan Tavares Pereira Batista; Joanna Maria Gonçalves de Souza-Fabjan; Nathália Oliveira Barbosa; Jeferson Ferreira da Fonseca; Felipe Zandonadi Brandão (Research in Veterinary Science, 2025)

Strategies and pathways to improve circularity in ceramic tile production - Sonia Javed; Sonia Conte; Chiara Molinari; Roberto Rosa; Anna Maria Ferrari; Michele Dondi; Chiara Zanelli (Journal of Cleaner Production, 2025)

Insulin resistance and cancer: molecular links and clinical perspectives - Alfredo Caturano; Enes Erul; Roberto Nilo; Davide Nilo; Vincenzo Russo; Luca Rinaldi; Carlo Acierno; Maria Gemelli; Riccardo Ricotta; Ferdinando Carlo Sasso; Antonio Giordano; Caterina Conte; et al. (Molecular and Cellular Biochemistry, 2025)

Spatial and seasonal variability of the contribution of sources to PM2.5, PM10 and their oxidative potential in different sites in a central Mediterranean area - Serena Potì; Eva Merico; Marianna Conte; Florin Unga; Daniela Cesari; Adelaide Dinoi; Anna Rita De Bartolomeo; Antonio Pennetta; Ermelinda Bloise; Giuseppe Deluca; Giuseppe Egidio De Benedetto; Roberto Ferrera; et al. (Science of The Total Environment, 2025)

How does UVC-LED combined vacuum packaging impact pea protein-based patties? - Júlia Moraes da Costa Marques; Bruno Dutra da Silva; Ana Júlia Bento do Amaral; Gabriela Hsieh Min Yi; Luiz Torres Neto; Juliana Fidelis dos Santos Ferreira; Maria Lúcia Guerra Monteiro; Carlos Adam Conte-Junior (Food and Humanity, 2025)

Spread of antimicrobial-resistant clones of the ESKAPEE group: From the clinical setting to hospital effluent - Damaris Krul; Bianca Ribeiro da Silva Negoseki; Adriele Celine Siqueira; Ana Paula de Oliveira Tomaz; Érika Medeiros dos Santos; Inayara de Sousa; Thais Muniz Vasconcelos; Isabelle Christine Rodrigues Marinho; Lavinia Nery Villa Stangler Arend; Dany Mesa; Danieli Conte; Libera Maria Dalla-Costa (Science of The Total Environment, 2025)

Modelling orexinergic system in ageing in the African turquoise killifish - Maria Raggio; Ivan Conte; Paolo de Girolamo; Livia D’Angelo (Biogerontology, 2025)
The orexinergic system is anatomically and functionally conserved in almost all vertebrates, and the role in healthy ageing and age-associated diseases has been studied in mammals. Here, we review the main findings on the age-related regulation of orexinergic system in mammals, including human patients and highlights how the fish Nothobranchius furzeri serves as an exceptional model to spearhead research and unravel the intricate mechanisms underlying orexinergic regulation during ageing. The ageing brain of this teleost is characterized by the presence of neurodegenerative processes similar to those associated with human pathologies rather than those of healthy ageing. We present an in-depth summary and discussion on the groundbreaking advances in understanding the neuroanatomical organization of the orexinergic system, its pivotal role in mammalian and fish models, and its profound involvement in healthy ageing and age-associated diseases.

A pipeline to predict the biosafety profile of putative biocontrol yeasts: Papiliotrema terrestris strain PT22AV as a case study - Davide Palmieri; Giuseppe Ianiri; Bruno Testa; Maria Chiara Guerrieri; Thomas Conte; Riccardo Aiese Cigliano; Carmine Del Grosso; Filippo De Curtis; Raffaello Castoria; Giuseppe Lima (BioControl, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

Genetic variants and phenotypic data curated for the CAGI6 intellectual disability panel challenge - Maria Cristina Aspromonte; Alessio Del Conte; Roberta Polli; Demetrio Baldo; Francesco Benedicenti; Elisa Bettella; Stefania Bigoni; Stefania Boni; Claudia Ciaccio; Stefano D’Arrigo; Ilaria Donati; Elisa Granocchio; et al. (Human Genetics, 2025)
Neurodevelopmental disorders (NDDs) are common conditions including clinically diverse and genetically heterogeneous diseases, such as intellectual disability, autism spectrum disorders, and epilepsy. The intricate genetic underpinnings of NDDs pose a formidable challenge, given their multifaceted genetic architecture and heterogeneous clinical presentations. This work delves into the intricate interplay between genetic variants and phenotypic manifestations in neurodevelopmental disorders, presenting a dataset curated for the Critical Assessment of Genome Interpretation (CAGI6) ID Panel Challenge. The CAGI6 competition serves as a platform for evaluating the efficacy of computational methods in predicting phenotypic outcomes from genetic data. In this study, a targeted gene panel sequencing has been used to investigate the genetic causes of NDDs in a cohort of 415 paediatric patients. We identified 60 pathogenic and 49 likely pathogenic variants in 102 individuals that accounted for 25% of NDD cases in the cohort. The most mutated genes were ANKRD11, MECP2, ARID1B, ASH1L, CHD8, KDM5C, MED12 and PTCHD 1 The majority of pathogenic variants were de novo, with some inherited from mildly affected parents. Loss-of-function variants were the most common type of pathogenic variant. In silico analysis tools were used to assess the potential impact of variants on splicing and structural/functional effects of missense variants. The study highlights the challenges in variant interpretation especially in cases with atypical phenotypic manifestations. Overall, this study provides valuable insights into the genetic causes of NDDs and emphasises the importance of understanding the underlying genetic factors for accurate diagnosis, and intervention development in neurodevelopmental conditions.

CAGI6 ID panel challenge: assessment of phenotype and variant predictions in 415 children with neurodevelopmental disorders (NDDs) - Maria Cristina Aspromonte; Alessio Del Conte; Shaowen Zhu; Wuwei Tan; Yang Shen; Yexian Zhang; Qi Li; Maggie Haitian Wang; Giulia Babbi; Samuele Bovo; Pier Luigi Martelli; Rita Casadio; et al. (Human Genetics, 2025)
The Genetics of Neurodevelopmental Disorders Lab in Padua provided a new intellectual disability (ID) Panel challenge for computational methods to predict patient phenotypes and their causal variants in the context of the Critical Assessment of the Genome Interpretation, 6th edition (CAGI6). Eight research teams submitted a total of 30 models to predict phenotypes based on the sequences of 74 genes (VCF format) in 415 pediatric patients affected by Neurodevelopmental Disorders (NDDs). NDDs are clinically and genetically heterogeneous conditions, with onset in infant age. Here, we assess the ability and accuracy of computational methods to predict comorbid phenotypes based on clinical features described in each patient and their causal variants. We also evaluated predictions for possible genetic causes in patients without a clear genetic diagnosis. Like the previous ID Panel challenge in CAGI5, seven clinical features (ID, ASD, ataxia, epilepsy, microcephaly, macrocephaly, hypotonia), and variants (Pathogenic/Likely Pathogenic, Variants of Uncertain Significance and Risk Factors) were provided. The phenotypic traits and variant data of 150 patients from the CAGI5 ID Panel Challenge were provided as training set for predictors. The CAGI6 challenge confirms CAGI5 results that predicting phenotypes from gene panel data is highly challenging, with AUC values close to random, and no method able to predict relevant variants with both high accuracy and precision. However, a significant improvement is noted for the best method, with recall increasing from 66% to 82%. Several groups also successfully predicted difficult-to-detect variants, emphasizing the importance of variants initially excluded by the Padua NDD Lab.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Exposure to Pyriproxyfen Impacts Heart Development Causing Tissue and Cellular Impairments, Heart Arrhythmia and Reduced Embryonic Growth - Maria Fernanda Conte Bernhardt; Nathália Ronconi-Krüger; Evelise Maria Nazari (Cardiovascular Toxicology, 2025)

Insights into the influence of intercropping and arbuscular mycorrhizal inoculation on two modern durum wheat cultivars and their associated microbiota - Elisa Zampieri; Fabiano Sillo; Giulio Metelli; Maria Alexandra Cucu; Vincenzo Montesano; Giulia Quagliata; Lena Philipp; Francesca Brescia; Adriano Conte; Luca Giovannini; Carmelo Mennone; Angelo Fiore; et al. (Biology and Fertility of Soils, 2025)

The influence of shallow-water methane emissions on foraminiferal assemblages: The case of Scoglio d’Affrica (Northern Tyrrhenian Sea, Mediterranean Sea) - Letizia Di Bella; Martina Pierdomenico; Aida Maria Conte; Irene Cornacchia; Tania Ruspandini; Daniele Spatola; Stanley Eugene Beaubien; Sabina Bigi; Alessia Conti; Giovanni Gaglianone; Michela Ingrassia; Francesco Latino Chiocci; et al. (Marine and Petroleum Geology, 2024)

Towards a personalized prediction, prevention and therapy of insomnia: gut microbiota profile can discriminate between paradoxical and objective insomnia in post-menopausal women - Monica Barone; Morena Martucci; Giuseppe Sciara; Maria Conte; Laura Smeldy Jurado Medina; Lorenzo Iattoni; Filomena Miele; Cristina Fonti; Claudio Franceschi; Patrizia Brigidi; Stefano Salvioli; Federica Provini; et al. (EPMA Journal, 2024)
Background Insomnia persists as a prevalent sleep disorder among middle-aged and older adults, significantly impacting quality of life and increasing susceptibility to age-related diseases. It is classified into objective insomnia (O-IN) and paradoxical insomnia (P-IN), where subjective and objective sleep assessments diverge. Current treatment regimens for both patient groups yield unsatisfactory outcomes. Consequently, investigating the neurophysiological distinctions between P-IN and O-IN is imperative for devising novel precision interventions aligned with primary prediction, targeted prevention, and personalized medicine (PPPM) principles. Working hypothesis and methodology. Given the emerging influence of gut microbiota (GM) on sleep physiology via the gut-brain axis, our study focused on characterizing the GM profiles of a well-characterized cohort of 96 Italian postmenopausal women, comprising 54 insomniac patients (18 O-IN and 36 P-IN) and 42 controls, through 16S rRNA amplicon sequencing. Associations were explored with general and clinical history, sleep patterns, stress, hematobiochemical parameters, and nutritional patterns. Results Distinctive GM profiles were unveiled between O-IN and P-IN patients. O-IN patients exhibited prominence in the Coriobacteriaceae family, including Collinsella and Adlercreutzia , along with Erysipelotrichaceae , Clostridium , and Pediococcus . Conversely, P-IN patients were mainly discriminated by Bacteroides , Staphylococcus , Carnobacterium , Pseudomonas , and respective families, along with Odoribacter . Conclusions These findings provide valuable insights into the microbiota-mediated mechanism of O-IN versus P-IN onset. GM profiling may thus serve as a tailored stratification criterion, enabling the identification of women at risk for specific insomnia subtypes and facilitating the development of integrated microbiota-based predictive diagnostics, targeted prevention, and personalized therapies, ultimately enhancing clinical effectiveness.

Unraveling effective modified atmosphere conditions to improve the quality of refrigerated stored dark and white muscle fish - Maria Lúcia Guerra Monteiro; Carlos Adam Conte-Junior (Innovative Food Science & Emerging Technologies, 2024)

High-risk clones of carbapenem resistant Klebsiella pneumoniae recovered from pediatric patients in Southern Brazil - Damaris Krul; Luiza Souza Rodrigues; Adriele Celine Siqueira; Dany Mesa; Érika Medeiros dos Santos; Thaís Muniz Vasconcelos; Regiane Nogueira Spalanzani; Rodrigo Cardoso; Marinei Campos Ricieri; Fábio de Araújo Motta; Danieli Conte; Libera Maria Dalla-Costa (Brazilian Journal of Microbiology, 2024)

Larval internal morphology of the introduced blowfly Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) - Ronaldo Roberto Tait Caleffe; Stefany Rodrigues de Oliveira; Eduardo Amat; Luz Miryam Gomez-Piñerez; Bruno Vinicius Daquila; Maria Claudia Colla Ruvulo-Takasusuki; Helio Conte (Zoologischer Anzeiger, 2024)

Fingerprinting based on spectral reflectance and chemometrics – An analytical approach aimed at combating the illegal trade of stingray meat in the Amazon - Jelmir Craveiro de Andrade; Adriano Teixeira de Oliveira; Maria Glauciney Fernandes Macedo Amazonas; Diego Galvan; Letícia Tessaro; Carlos Adam Conte-Junior (Food Chemistry, 2024)

Optimized UVC-LED condition to improve the shelf life of vacuum-packed refrigerated stored rainbow trout (Oncorhynchus mykiss) fillets - Maria Lúcia Guerra Monteiro; Luiz Torres Neto; Yhan da Silva Mutz; Carolina Ramos da Silva; Amanda Cristina Corrêa Cardoso; Carlos Adam Conte-Junior (Food Control, 2024)

Exploring high hydrostatic pressure for enhancing the preservation of white and dark muscle fish fillets stored at different packaging systems under refrigeration - Maria Lúcia G. Monteiro; Denes K.A. Rosário; Luiz Torres Neto; Carlos A. Conte-Junior (Food Control, 2024)

Optimizing Salmonella Enteritidis inactivation in Salmon (Salmo salar) by the combined treatment of UV-LED and of Origanum vulgare essential oil nanoemulsion - Yhan S. Mutz; Carolina Ramos; Maria Lucia Guerra Monteiro; Bruno Dutra da Silva; Luiz Torres; Leticia Tessaro; Carlos A. Conte-Junior (Food Control, 2023)

Correction to: Geometric Reliability of Super-Resolution Reconstructed Images from Clinical Fetal MRI in the Second Trimester - Tommaso Ciceri; Letizia Squarcina; Alessandro Pigoni; Adele Ferro; Florian Montano; Alessandra Bertoldo; Nicola Persico; Simona Boito; Fabio Maria Triulzi; Giorgio Conte; Paolo Brambilla; Denis Peruzzo (Neuroinformatics, 2023)

Breast Cancer Prevention: The Key Role of Population Screening, Breast Self-Examination (BSE) and Technological Tools. Survey of Italian Women - Luana Conte; Giorgio De Nunzio; Roberto Lupo; Matilde Mieli; Alessia Lezzi; Elsa Vitale; Maria Chiara Carriero; Antonino Calabrò; Maicol Carvello; Ivan Rubbi; Massimo Federico (Journal of Cancer Education, 2023)
Breast cancer is the most common tumor among women worldwide and still remains the leading cause of death in women in Italy. Although survival from this pathology has increased, this disease and its treatment can have lasting or delayed effects that can greatly affect a woman's quality of life. Primary and secondary prevention are currently the best strategies to combat this cancer: improved lifestyle, early adherence to screening, Breast Self-Examination (BSE), and even now the use of technology, have become among the most important tools to ensure increasingly early diagnosis of this disease, which is a major cause of suffering and premature mortality in women. Indeed, early diagnosis of the disease can lead to a good prognosis and a high survival rate. This study investigates the attitude of Italian women to perform clinical checkups aimed at cancer prevention, particularly adherence to free screening programs offered by the National Health Service (NHS) for women in the 50–69 age group. The knowledge, use and emotional approach toward BSE as a screening tool and the use of dedicated apps for this purpose are also investigated. Low adherence to screening programs, lack of BSE practice, and nonuse of dedicated apps are just some of the results observed in this study. Therefore, it becomes essential to spread the culture of prevention, cancer awareness and the importance of screening throughout life.

A Comparison of the Efficacy of Two Omeprazole Formulations in the Treatment of Equine Gastric Ulcer Syndrome in Racehorses: A Blinded, Randomized Clinical Trial - Sara Busechian; Maria Beatrice Conti; Micaela Sgorbini; Giuseppe Conte; Maria Chiara Marchesi; Camillo Pieramati; Francesco Zappulla; Valentina Vitale; Fabrizio Rueca (Journal of Equine Veterinary Science, 2023)

Geometric Reliability of Super-Resolution Reconstructed Images from Clinical Fetal MRI in the Second Trimester - Tommaso Ciceri; Letizia Squarcina; Alessandro Pigoni; Adele Ferro; Florian Montano; Alessandra Bertoldo; Nicola Persico; Simona Boito; Fabio Maria Triulzi; Giorgio Conte; Paolo Brambilla; Denis Peruzzo (Neuroinformatics, 2023)
Fetal Magnetic Resonance Imaging (MRI) is an important noninvasive diagnostic tool to characterize the central nervous system (CNS) development, significantly contributing to pregnancy management. In clinical practice, fetal MRI of the brain includes the acquisition of fast anatomical sequences over different planes on which several biometric measurements are manually extracted. Recently, modern toolkits use the acquired two-dimensional (2D) images to reconstruct a Super-Resolution (SR) isotropic volume of the brain, enabling three-dimensional (3D) analysis of the fetal CNS. We analyzed 17 fetal MR exams performed in the second trimester, including orthogonal T2-weighted (T2w) Turbo Spin Echo (TSE) and balanced Fast Field Echo (b-FFE) sequences. For each subject and type of sequence, three distinct high-resolution volumes were reconstructed via NiftyMIC, MIALSRTK, and SVRTK toolkits. Fifteen biometric measurements were assessed both on the acquired 2D images and SR reconstructed volumes, and compared using Passing-Bablok regression, Bland-Altman plot analysis, and statistical tests. Results indicate that NiftyMIC and MIALSRTK provide reliable SR reconstructed volumes, suitable for biometric assessments. NiftyMIC also improves the operator intraclass correlation coefficient on the quantitative biometric measures with respect to the acquired 2D images. In addition, TSE sequences lead to more robust fetal brain reconstructions against intensity artifacts compared to b-FFE sequences, despite the latter exhibiting more defined anatomical details. Our findings strengthen the adoption of automatic toolkits for fetal brain reconstructions to perform biometry evaluations of fetal brain development over common clinical MR at an early pregnancy stage.

Remdesivir treatment and clinical outcome in non-severe hospitalized COVID-19 patients: a propensity score matching multicenter Italian hospital experience - Emilio Attena; Alfredo Caturano; Anna Annunziata; Alberto Enrico Maraolo; Annunziata De Rosa; Francesco Maria Fusco; Geza Halasz; Valeria Dall’Ospedale; Maddalena Conte; Valentina Parisi; Raffaele Galiero; Ferdinando Carlo Sasso; et al. (European Journal of Clinical Pharmacology, 2023)
Introduction Remdesivir exerts positive effects on clinical improvement, even though it seems not to affect mortality among COVID-19 patients; moreover, it was associated with the occurence of marked bradycardia. Methods We retrospectively evaluated 989 consecutive patients with non-severe COVID-19 (SpO 2 ≥ 94% on room air) admitted from October 2020 to July 2021 at five Italian hospitals. Propensity score matching allowed to obtain a comparable control group. Primary endpoints were bradycardia onset (heart rate < 50 bpm), acute respiratory distress syndrome (ARDS) in need of intubation and mortality. Results A total of 200 patients (20.2%) received remdesivir, while 789 standard of care (79.8%). In the matched cohorts, severe ARDS in need of intubation was experienced by 70 patients (17.5%), significantly higher in the control group (68% vs. 31%; p < 0.0001). Conversely, bradycardia, experienced by 53 patients (12%), was significantly higher in the remdesivir subgroup (20% vs. 1.1%; p < 0.0001). During follow-up, all-cause mortality was 15% ( N = 62), significantly higher in the control group (76% vs. 24%; log-rank p < 0.0001), as shown at the Kaplan–Meier (KM) analysis. KM furthermore showed a significantly higher risk of severe ARDS in need of intubation among controls (log-rank p < 0.001), while an increased risk of bradycardia onset in the remdesivir group (log-rank p < 0.001). Multivariable logistic regression showed a protective role of remdesivir for both ARDS in need of intubation (OR 0.50, 95%CI 0.29–0.85; p = 0.01) and mortality (OR 0.18, 95%CI 0.09–0.39; p < 0.0001). Conclusions Remdesivir treatment emerged as associated with reduced risk of severe acute respiratory distress syndrome in need of intubation and mortality. Remdesivir-induced bradycardia was not associated with worse outcome.

Prevalence and bleeding risk associated with the concomitant use of direct oral anticoagulants and antiarrhythmic drugs in patients with atrial fibrillation, based on the French healthcare insurance database - Laëtitia Gosselin; Ana-Maria Vilcu; Cécile Souty; Olivier Steichen; Titouan Launay; Cécile Conte; Béatrice Saint-Salvi; Clément Turbelin; Marianne Sarazin; Thierry Blanchon; Thomas Hanslik; Maryse Lapeyre-Mestre; et al. (European Journal of Clinical Pharmacology, 2023)

An overview on in vitro and in vivo antiviral activity of lactoferrin: its efficacy against SARS-CoV-2 infection - Luigi Rosa; Antimo Cutone; Maria Pia Conte; Elena Campione; Luca Bianchi; Piera Valenti (BioMetals, 2023)

Effect of bovine lactoferrin on recurrent urinary tract infections: in vitro and in vivo evidences - Antonietta Lucia Conte; Catia Longhi; Maria Pia Conte; Anna Maria Costanzo; Rosalba Paesano; Stefano Santangeli; Francesco Venditto; Giovanni Tripepi; Enrico Naldi; Giuditta Pollio; Valeria Cavallini; Marco Marrani; et al. (BioMetals, 2023)

Characterisation of the correlations between oxidative potential and in vitro biological effects of PM10 at three sites in the central Mediterranean - Maria Rachele Guascito; Maria Giulia Lionetto; Franco Mazzotta; Marianna Conte; Maria Elena Giordano; Roberto Caricato; Anna Rita De Bartolomeo; Adelaide Dinoi; Daniela Cesari; Eva Merico; Laura Mazzotta; Daniele Contini (Journal of Hazardous Materials, 2023)

Concentration and size distribution of atmospheric particles in southern Italy during COVID-19 lockdown period - Marianna Conte; Adelaide Dinoi; Fabio Massimo Grasso; Eva Merico; Maria Rachele Guascito; Daniele Contini (Atmospheric Environment, 2023)

Heavy metal background levels and pollution temporal trend assessment within the marine sediments facing a brownfield area (Gulf of Pozzuoli, Southern Italy) - Giovanna Armiento; Mattia Barsanti; Raffaela Caprioli; Salvatore Chiavarini; Fabio Conte; Cinzia Crovato; Maurizio De Cassan; Ivana Delbono; Maria R. Montereali; Elisa Nardi; Luisa Parrella; Massimo Pezza; et al. (Environmental Monitoring and Assessment, 2022)
In this study, site-specific natural background levels (NBLs) were determined for 18 elements (Al, As, Be, Cd, Co, Cu, Cr, Fe, Hg, K, Mn, Mo, Ni, Pb, Tl, U, V, and Zn) in two sediment cores collected offshore the Bagnoli-Coroglio brownfield site (Gulf of Pozzuoli, southern Italy) to accurately assess the degree of contamination and the historical trends in Heavy Metals (HMs) enrichment. This objective was pursued taking in account the high temporal and spatial variability of the geochemical properties of the area due to the local geothermal activity. Moreover, the temporal variation of Polycyclic Aromatic Hydrocarbons (PAHs) was investigated. 226 Ra was used as an extraordinary marker to confirm 210 Pb dating. It especially allowed defining the geochronological framework of the sediment core closer the brownfield up to around 1500, providing compelling support to correlate the investigated elements’ occurrences with natural geogenic dynamic. Sediment samples were accurately dated and analyzed for chemical and particle size composition. The contamination factor (Cf) and the pollution load index (PLI) showed very high enrichment of Cd, Cu, Hg, Pb, and Zn. The contamination profiles of HMs and PAHs follow the same pattern in both sediment cores, increasing from deep to upper layers. The highest contamination levels for HMs and PAHs were observed between 10 and 30 cm, corresponding to the periods of most intense industrial activity. Decreasing trends of pollutants were observed in the surface layers (0–10 cm), probably affected by a natural attenuation process due to the cessation of industrial activities.

Traceological analysis of lithics from the Camel Site, al-Jawf, Saudi Arabia: an experimental approach to identifying mineral processing activities using silcrete tools - Yamandú H. Hilbert; Ignacio Clemente-Conte; Rémy Crassard; Guillaume Charloux; Maria Guagnin; Abdullah M. AlSharekh (Archaeological and Anthropological Sciences, 2022)
The Camel Site is in the north of Saudi Arabia in the province of al-Jawf. It is characterised by three decaying sandstone hillocks with life-sized 3D engravings (or reliefs) of camels and equids likely carved during later prehistory. A survey in the central area of the site identified clusters of flakes and other flintknapping remains in the lower areas between the sandstone spurs and larger silcrete tools directly underneath the animal depictions. Some of these tools presented abraded edges, possibly from prolonged contact with the soft and abrasive sandstone that constitutes the rock spurs where the animals were carved. Experiments were performed to test this hypothesis and have a reference collection for further traceological analysis. The chaine opératoire of the experimental engraving tools, from raw material procurement, tool manufacture and use, reuse and discard, was conducted with locally available materials comparable to the archaeological specimens. Specific experimental variables, including how the force was applied, in what direction the movement took place and the orientation of the stone tool during the experiment, were also recorded. Macro- and microscopic analyses of the experimental collection and a sample of archaeological artefacts seem to show that the ancient tools found on the surface were probably used to make the camelid and equid reliefs at the site.

The elderly at risk: aldosterone as modulator of the immune response to SARS-CoV-2 infection - Pasquale Campana; Maria Emiliana Palaia; Maddalena Conte; Teresa Cante; Laura Petraglia; Grazia Daniela Femminella; Valentina Parisi; Dario Leosco (GeroScience, 2022)

Disease-specific plasma levels of mitokines FGF21, GDF15, and Humanin in type II diabetes and Alzheimer’s disease in comparison with healthy aging - Maria Conte; Jacopo Sabbatinelli; Antonio Chiariello; Morena Martucci; Aurelia Santoro; Daniela Monti; Marina Arcaro; Daniela Galimberti; Elio Scarpini; Anna Rita Bonfigli; Angelica Giuliani; Fabiola Olivieri; et al. (GeroScience, 2021)
Fibroblast Growth Factor 21 (FGF21), Growth Differentiation Factor 15 (GDF15), and Humanin (HN) are mitochondrial stress-related mitokines, whose role in health and disease is still debated. In this study, we confirmed that their plasma levels are positively correlated with age in healthy subjects. However, when looking at patients with type 2 diabetes (T2D) or Alzheimer’s disease (AD), two age-related diseases sharing a mitochondrial impairment, we found that GDF15 is elevated in T2D but not in AD and represents a risk factor for T2D complications, while FGF21 and HN are lower in AD but not in T2D. Moreover, FGF21 reaches the highest levels in centenarian’ offspring, a model of successful aging. As a whole, these data indicate that (i) the adaptive mitokine response observed in healthy aging is lost in age-related diseases, (ii) a common expression pattern of mitokines does not emerge in T2D and AD, suggesting an unpredicted complexity and disease-specificity, and (iii) FGF21 emerges as a candidate marker of healthy aging.

Use of the French healthcare insurance database to estimate the prevalence of exposure to potential drug-drug interactions - Cécile Souty; Titouan Launay; Olivier Steichen; Cécile Conte; Clément Turbelin; Marianne Sarazin; Ana-Maria Vilcu; Louise Rossignol; Thierry Blanchon; Maryse Lapeyre-Mestre; Thomas Hanslik (European Journal of Clinical Pharmacology, 2020)

Mitochondria, immunosenescence and inflammaging: a role for mitokines? - Maria Conte; Morena Martucci; Antonio Chiariello; Claudio Franceschi; Stefano Salvioli (Seminars in Immunopathology, 2020)
A global reshaping of the immune responses occurs with ageing, indicated as immunosenescence, where mitochondria and mitochondrial metabolism play an important role. However, much less is known about the role of mitochondrial stress response in this reshaping and in particular of the molecules induced by such response, collectively indicated as mitokines. In this review, we summarize the current knowledge on the role of mitokines in modulating immune response and inflammation focusing on GDF15, FGF21 and humanin and their possible involvement in the chronic age-related low-grade inflammation dubbed inflammaging. Although many aspects of their biology are still controversial, available data suggest that these mitokines have an anti-inflammatory role and increase with age. Therefore, we hypothesize that they can be considered part of an adaptive and integrated immune-metabolic mechanism activated by mitochondrial dysfunction that acts within the framework of a larger anti-inflammatory network aimed at controlling both acute inflammation and inflammaging.

The smell of longevity: a combination of Volatile Organic Compounds (VOCs) can discriminate centenarians and their offspring from age-matched subjects and young controls - Maria Conte; Giuseppe Conte; Morena Martucci; Daniela Monti; Laura Casarosa; Andrea Serra; Marcello Mele; Claudio Franceschi; Stefano Salvioli (GeroScience, 2020)

Nutritional Improvement and Consumer Perspective of Fish Nuggets with Partial Substitution of Wheat Flour Coating by Fish ( Priacanthus arenatus , Cuvier, 1829) Waste Flour - Bruno de Carvalho Bonfim; Maria Lúcia Guerra Monteiro; Alejandra Filippo Gonzalez Neves do Santos; Juliana dos Santos Vilar; Carlos Adam Conte-Junior (Journal of Aquatic Food Product Technology, 2020)

Metal Resistance in Bacteria from Contaminated Arctic Sediment is Driven by Metal Local Inputs - Simona Caputo; Maria Papale; Carmen Rizzo; Stefania Giannarelli; Antonella Conte; Federica Moscheo; Marco Graziano; Paul Eric Aspholm; Massimo Onor; Emilio De Domenico; Stefano Miserocchi; Luigi Michaud; et al. (Archives of Environmental Contamination and Toxicology, 2019)

Physico-chemical properties influence the functions and efficacy of commercial bovine lactoferrins - Luigi Rosa; Antimo Cutone; Maria Stefania Lepanto; Mellani Jinnett Scotti; Maria Pia Conte; Rosalba Paesano; Piera Valenti (BioMetals, 2018)

Effect of the UV-C Radiation on Shelf Life of Vacuum-Packed Refrigerated Pirarucu ( Arapaima gigas ) Fillets - Júlia de Souza Lira Santos; Eliane Teixeira Mársico; Môsar Lemos; Miguel Antônio Cinquini; Flávio Alves da Silva; Yasmin Bugini Dutra; Robson Maia Franco; Carlos Adam Conte Junior; Maria Lúcia Guerra Monteiro (Journal of Aquatic Food Product Technology, 2018)

Dentatorubro-Pallidoluysian Atrophy (DRPLA) among 700 Families with Ataxia in Brazil - Pedro Braga-Neto; José Luiz Pedroso; Gabriel Vasata Furtado; Tailise Conte Gheno; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim; Orlando G. P. Barsottini (The Cerebellum, 2017)

Idiopathic hypertrophic pachymeningitis: an autoimmune IgG4-related disease - Armando De Virgilio; Marco de Vincentiis; Maurizio Inghilleri; Giovanni Fabrini; Michela Conte; Andrea Gallo; Maria Ida Rizzo; Antonio Greco (Immunologic Research, 2017)

Glaucoma: recent advances in the involvement of autoimmunity - Maria Ida Rizzo; Antonio Greco; Armando De Virgilio; Andrea Gallo; Luciano Taverniti; Massimo Fusconi; Michela Conte; Giulio Pagliuca; Rosaria Turchetta; Marco de Vincentiis (Immunologic Research, 2017)

Erratum to: Differential expression of perilipin 2 and 5 in human skeletal muscle during aging and their association with atrophy-related genes - Maria Conte; Francesco Vasuri; Enrico Bertaggia; Andrea Armani; Aurelia Santoro; Elena Bellavista; Alessio Degiovanni; Antonia D’Errico-Grigioni; Giovanni Trisolino; Miriam Capri; Martino V. Franchi; Marco V. Narici; et al. (Biogerontology, 2015)

Differential expression of perilipin 2 and 5 in human skeletal muscle during aging and their association with atrophy-related genes - Maria Conte; Francesco Vasuri; Enrico Bertaggia; Andrea Armani; Aurelia Santoro; Elena Bellavista; Alessio Degiovanni; Antonia D’Errico-Grigioni; Giovanni Trisolino; Miriam Capri; Martino V. Franchi; Marco V. Narici; et al. (Biogerontology, 2015)

Protein kinase C theta (PKCθ) modulates the ClC-1 chloride channel activity and skeletal muscle phenotype: a biophysical and gene expression study in mouse models lacking the PKCθ - Giulia Maria Camerino; Marina Bouchè; Michela De Bellis; Maria Cannone; Antonella Liantonio; Kejla Musaraj; Rossella Romano; Piera Smeriglio; Luca Madaro; Arcangela Giustino; Annamaria De Luca; Jean-François Desaphy; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Lactoferrin differently modulates the inflammatory response in epithelial models mimicking human inflammatory and infectious diseases - Alessandra Frioni; Maria Pia Conte; Antimo Cutone; Catia Longhi; Giovanni Musci; Maria Carmela Bonaccorsi di Patti; Tiziana Natalizi; Massimiliano Marazzato; Maria Stefania Lepanto; Patrizia Puddu; Rosalba Paesano; Piera Valenti; et al. (BioMetals, 2014)

Spinocerebellar Ataxias in Brazil—Frequencies and Modulating Effects of Related Genes - Raphael Machado de Castilhos; Gabriel Vasata Furtado; Tailise Conte Gheno; Paola Schaeffer; Aline Russo; Orlando Barsottini; José Luiz Pedroso; Diego Z. Salarini; Fernando Regla Vargas; Maria Angélica de Faria Domingues d Lima; Clécio Godeiro; Luiz Carlos Santana-da-Silva; et al. (The Cerebellum, 2014)

Adipose stromal/stem cells assist fat transplantation reducing necrosis and increasing graft performance - Maria Serena Piccinno; Elena Veronesi; Pietro Loschi; Marco Pignatti; Alba Murgia; Giulia Grisendi; Ilaria Castelli; Daniela Bernabei; Olivia Candini; Pierfranco Conte; Paolo Paolucci; Edwin M. Horwitz; et al. (Apoptosis, 2013)

Age-dependent alteration in muscle regeneration: the critical role of tissue niche - Laura Barberi; Bianca Maria Scicchitano; Manuela De Rossi; Anne Bigot; Stephanie Duguez; Aurore Wielgosik; Claire Stewart; Jamie McPhee; Maria Conte; Marco Narici; Claudio Franceschi; Vincent Mouly; et al. (Biogerontology, 2013)

Climate change and the spread of vector‐borne diseases: using approximate B ayesian computation to compare invasion scenarios for the bluetongue virus vector C ulicoides imicola in I taly - Patrick Mardulyn; Maria Goffredo; Annamaria Conte; Guy Hendrickx; Rudolf Meiswinkel; Thomas Balenghien; Soufien Sghaier; Youssef Lohr; Marius Gilbert (Molecular Ecology, 2013)
Bluetongue ( BT ) is a commonly cited example of a disease with a distribution believed to have recently expanded in response to global warming. The BT virus is transmitted to ruminants by biting midges of the genus C ulicoides , and it has been hypothesized that the emergence of BT in Mediterranean Europe during the last two decades is a consequence of the recent colonization of the region by C ulicoides imicola and linked to climate change. To better understand the mechanism responsible for the northward spread of BT , we tested the hypothesis of a recent colonization of Italy by C . imicola , by obtaining samples from more than 60 localities across I taly, C orsica, S outhern F rance, and N orthern A frica (the hypothesized source point for the recent invasion of C . imicola ), and by genotyping them with 10 newly identified microsatellite loci. The patterns of genetic variation within and among the sampled populations were characterized and used in a rigorous approximate B ayesian computation framework to compare three competing historical hypotheses related to the arrival and establishment of C . imicola in I taly. The hypothesis of an ancient presence of the insect vector was strongly favoured by this analysis, with an associated P ≥ 99%, suggesting that causes other than the northward range expansion of C . imicola may have supported the emergence of BT in southern Europe. Overall, this study illustrates the potential of molecular genetic markers for exploring the assumed link between climate change and the spread of diseases.

Ethical aspects of aging research - Enn Seppet; Mati Pääsuke; Maria Conte; Miriam Capri; Claudio Franceschi (Biogerontology, 2011)

Analysis by two-dimensional Blue Native/SDS-PAGE of membrane protein alterations in rat soleus muscle after hindlimb unloading - Davide Basco; Grazia Paola Nicchia; Jean-François Desaphy; Diana Conte Camerino; Antonio Frigeri; Maria Svelto (European Journal of Applied Physiology, 2010)

Late-Alpine rodingitization in the Bellecombe meta-ophiolites (Aosta Valley, Italian Western Alps): evidence from mineral assemblages and serpentinization-derived H 2 -bearing brine - Simona Ferrando; Maria Luce Frezzotti; Paolo Orione; Riccardo Carlo Conte; Roberto Compagnoni (International Geology Review, 2010)

Effect of microgravity on gene expression in mouse brain - Antonio Frigeri; Dumitru A. Iacobas; Sanda Iacobas; Grazia Paola Nicchia; Jean Francois Desaphy; Diana Conte Camerino; Maria Svelto; David C. Spray (Experimental Brain Research, 2008)

Diagnostic identification of malignant cells in the cerebrospinal fluid by tumor-specific qRT-PCR - Cristina Rosanda; Claudio Gambini; Barbara Carlini; Massimo Conte; Bruno De Bernardi; Alberto Garaventa; Maria Valeria Corrias (Clinical & Experimental Metastasis, 2006)

Influence of retigabine on the anticonvulsant activity of some antiepileptic drugs against audiogenic seizures in DBA/2 mice - Giovambattista De Sarro; Eugenio Donato Di Paola; Giuseppe Conte; Maria Patrizia Pasculli; Angela De Sarro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

The solution structure of a monomeric, reduced form of human copper,zinc superoxide dismutase bearing the same charge as the native protein - Lucia Banci; I. Bertini; R. Del Conte; Roberto Fadin; Stefano Mangani; Maria Silvia Viezzoli (JBIC Journal of Biological Inorganic Chemistry, 1999)